IL-1β (Interleukin-1β) and TNF-α (Tumor Necrosis Factor-α) Impact Abdominal Aortic Aneurysm Formation by Differential Effects on Macrophage Polarization. Issue 2 (February 2018) - Batra, Rishi; Suh, Melissa K.; Carson, Jeffrey S.; Dale, Matthew A.; Meisinger, Trevor M.; Fitzgerald, Matthew; Opperman, Patrick J.; Luo, Jiangtao; Pipinos, Iraklis I.; Xiong, Wanfen; Baxter, B. Timothy
Abstract : Objective—: Abdominal aortic aneurysms are inflammatory in nature and are associated with some risk factors that also lead to atherosclerotic occlusive disease, most notably smoking. The purpose of our study was to identify differential cytokine expression in patients with abdominal aortic aneurysm and those with atherosclerotic occlusive disease. Based on this analysis, we further explored and compared the mechanism of action of IL (interleukin)-1β versus TNF-α (tumor necrosis factor-α) in abdominal aortic aneurysm formation. Approach and Results—: IL-1β was differentially expressed in human plasma with lower levels detected in patients with abdominal aortic aneurysm compared with matched atherosclerotic controls. We further explored its mechanism of action using a murine model and cell culture. Genetic deletion of IL-1β and IL-1R did not inhibit aneurysm formation or decrease MMP (matrix metalloproteinase) expression. The effects of IL-1β deletion on M1 macrophage polarization were compared with another proinflammatory cytokine, TNF-α. Bone marrow-derived macrophages from IL-1β −/− and TNF-α −/− mice were polarized to an M1 phenotype. TNF-α deletion, but not IL-1β deletion, inhibited M1 macrophage polarization. Infusion of M1 polarized TNF-α −/− macrophages inhibited aortic diameter growth; no inhibitory effect was seen in mice infused with M1 polarized IL-1β −/− macrophages. Conclusions—: Although IL-1β is a proinflammatory cytokine, its effects on aneurysm formation and macrophage polarization differ from TNF-α. The differential effects of IL-1β and TNF-α inhibition are related to M1/M2 macrophage polarization and this may account for the differences in clinical efficacy of IL-1β and TNF-α antibody therapies in management of inflammatory diseases. Abstract : Supplemental Digital Content is available in the text.